A taxonomic revision of Monolepta pallidula species group in Taiwan (Coleoptera: Chrysomelidae: Galerucinae) - Lee, Chi-Feng (Zootaxa, 2009)
The species belonging to the Monolepta pallidula species group are revised. Two species are recognized as valid: Monolepta sauteri Chûjô and M. kuroheri Kimoto. Taiwanese populations of Monolepta pallidula (Baly) are a distinct species different from the true M. pallidula. Thus Monolepta gracilipes Chûjô, a junior synonym of M. pallidula from Taiwan, is an available name and should be reinstated. A new species, Monolepta tsoui, is described with delimitation of color variation from its allied species, M. gracilipes. A lectotype is designated for Monolepta gracilipes Chûjô. A key to the species of the species group is provided.